Improvement of the High-Performance Al-Doped LiNi1/3Co1/3Mn1/3O2 Cathode Material for New Electro-Optical Conversion Devices - Gao, Yumei; Yuan, Wangran; Dou, Xinqi (Frontiers in Physics, 2021)
The ternary cathode material LiNi1/3Co1/3Mn1/3O2 has been extensively focused on as the power sources for new electro-optical conversion devices and lithium-ion batteries. To improve the electrochemical performance, Al doping is one of the effective strategies. Based on the density functional theory of first-principles, the band gap, volume, partial density of states, lithiation formation energy, electron density difference, and electrons’ potential energy of Li1.0-xAlxNi1/3Co1/3Mn1/3O2 were simulated and analyzed with Materials Studio, Nanodcal and Matlab. Results show that Li0.9Al0.1Ni1/3Co1/3Mn1/3O2 has a better conductivity and cycling capability. The potential energy maps of Li1.0-xAlxNi1/3Co1/3Mn1/3O2 simulated in Matlab indicate that the rate capability of LiNi1/3Co1/3Mn1/3O2 is promoted after Al doping. Our theoretical advice could be an important choice for the power application of new optoelectronic devices. In addition, our methods could provide some theoretical guidance for the subsequent electrochemical performance investigations on doping of optoelectronic devices or lithium-ion battery materials.